PELAKSANAAN KAMPUS MENGAJAR DI SDIT ASHABUL KAHFI KABUPATEN DELISERDANG - Joni Wilson Sitopu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The Teaching Campus Program is part of the Merdeka Campus program of the Ministry of Education and Culture of the Republic of Indonesia, in its implementation, it aims to make students later have the ability to master a variety of sciences, namely to develop insight and gain experience outside the classroom through teaching and learning activities at school. Activities carried out by DPL and students aim to; 1. Helping learning during a pandemic; 2. Helping teachers to teach; 3. Assist in strengthening literacy and numeracy learning; 4. Helping learning using technology adaptation and its application for schools, teachers and students; 5. Assist in the preparation of a better administrative system. The research subject is SDIT Ashabul Kahfi, Deliserdang Regency. The object of research is the residents of SDIT Ashabul Kahfi in the implementation of learning. The research method used is descriptive qualitative method, namely; 1. Explain how the picture of what happened to the school during the implementation of campus teaching, and 2. Explain a series of problems that occur in the implementation of the learning process. Data collection techniques in this study were observation, interviews, and documentation. Based on the results of the final analysis of the program obtained; 1. Provide changes in the teaching and learning process, 2. Provide feedback to students, from not knowing how to read and count to knowing and increase enthusiasm for learning, 3. Installing and using infocus in the classroom is used to support student learning activities, teacher meetings , and training, 4. Evaluating and tidying up the administration of teacher and school assessments is very helpful for schools at SDIT Ashabul Kahfi.